The Recommended in Mysticism: The Innovation of Guidance or the Innovation of Misguidance? - حسن رمضانی (حکمت اسرا)
Due to some expedients and for the administration of the disciples and their better education, mystics established certain regulations and customs, which became known as "Mustahsanât" (the recommended). Some of the opponents of mysticism consider the forgery of these customs as an example of "innovation" in religion, which according to some of the hadiths is prohibited and its subject deserves punishment. In this paper, using an analytical method, based on the definition of heresy/innovation on the part of the scholars of Islamic sciences and the analysis of some verses and transmitted traditions, we conclude that, though according to the Prophetic tradition innovation in the religion is prohibited and its subject deserves punishment, the innovation that doesn’t violate religious orders and for which generally can be found a religious documentary is a kind of commendable innovation or guidance, not a disapproved innovation or misguidance. Not only commendable innovations aren’t forbidden, but also in some cases, according to the Prophetic traditions, they are permissible if they constitute a good tradition, and even they could be obligatory for the maintenance of Muslims and the religion of Islam. Accordingly, the recommended in mysticism are commendable innovations not disapproved ones, because they are based on the expedients of the mystical journey. Of course, the abuses and extremes that are sometimes made by some devious and ignorant Sufis about the recommended customs are condemned due to the consequences of excesses or extremes, but should not be considered principally as examples of disapproved innovations and so prohibited.